The Influence of the Implementation of the Game-Based Learning Model (Squid Games) on Learning Outcomes in the Indonesian Language Education Subject for Third Grade Students at SD Negeri Bangsal 3, Kediri City - Hanifa Rahma Yulisa (Insight School Academy, 2025)
Introduction to The Problem: This community service activity is carried out with the aim of improving student learning outcomes through the Game-Based Learning model (Squid Game). Purpose: The purpose of this study is to improve student learning outcomes through the Game-Based Learning model (Squid Game). Design/methods/approach: The method used in this study is a quantitative approach, with the research target being 29 third-grade elementary school students. Data collection for this study was conducted over a period of 1 month. Findings: The results and findings of this study indicate that the implementation of the Game-Based Learning model (Squid Games) can improve learning outcomes in the Indonesian Language Education subject for third-grade students at SD Negeri Bangsal 3, Kediri City.